The complete mitochondrial genome of click beetle Agrypnus sp. (Coleoptera: Elateridae) and phylogenetic analysis. Issue 2 (3rd July 2019) - Du, Yimin; Liu, Xinjun; Long, Yunfei; Cheng, Shuyuan; Zhong, Balian
Abstract: Larvae of click beetles are the most important soil-dwelling agricultural pests and are abundant throughout the world. Agrypnus sp. belongs to the subfamily Agrypninae of Elateridae. Here, we sequenced and annotated the complete mitochondrial genome (mitogenome) of Agrypnus sp., the new representative of the mitogenome of the subfamily. This mitogenome was 16, 056 bp long and encoded 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), and two ribosomal RNA unit genes (rRNAs). Gene order was conserved and identical to most other previously sequenced Elateridae. The nucleotide composition biases towards A and T, which together made up 70.8% of the entirety. Phylogenetic analysis based on 13 PCGs sequences showed that Agrypnus sp. got together with the same subfamily species Pyrophorus divergens, Pyrearinus termitilluminans, Ignelater luminosus, and Hapsodrilus ignifer with high support value.